THE ROLE OF PROFITABILITY IN MEDICATING THE EFFECT OF THE CAPITAL STRUCTURE OF COMPANY VALUE IN IDX PERIOD 2013-2017 - Bulan Windu Kirana, I Gusti Ayu Agung; Badjra, Ida Bagus (E-Jurnal Manajemen, 2018)
The value of the company reflects the prosperity for the owners of the company and creates the welfare of shareholders. In order for investors to get a high score then need to note the factors that affect the value of the company. This research was conducted in Consumer Goods Industry sector in Indonesia Stock Exchange with total population of 26 companies. The number of samples taken as many as 12 companies with purposive sampling method. Technique Analysis of data used is path analysis. Based on the results of the analysis found that the capital structure has a positive and significant impact on corporate value, profitability has a positive and significant impact on firm value. This means that the capital structure plays an important role for the company in increasing profitability, so the addition of proportion of debt that can increase profitability can be used to obtain higher corporate value. Keywords: capital structure, profitability, firm value